MESSIANISME DALAM GERAKAN SOSIAL-KEAGAMAAN DI INDONESIA - Arif Subekti (Historiography: Journal of Indonesian History and Education, 2021)
This article aims to explore inter-connection between messianism and socio-religio movement in Indonesian history. Politics of the past, struggling to gain education, and religion culture shape today’s history, regarding the big man born by those power where has had history driven by. In the name of expression of peripheral area amongst severe pristine and well-known religion: i.e. Hindhu, Buddha, Islam, Protestant and Catholic; the believe of savior coming to save the world were the heart of messianism. The idea of messianism coloured the Indonesian history, until recent era.Artikel ini bertujuan untuk menggambarkan kelit-kelindan antara gerakan sosial-keagamaan, dengan gagasan messianisme. Dinamika politik di masa lalu, perjuangan untuk mengakses pendidikan, serta tafsir agama sedikit banyak membentuk sejarah masa kini, dengan menempatkan tokoh-tokoh besar sebagai pusat arah sejarah bergerak. Atas nama ekspresi keagamaan di wilayah pinggiran, di antara pusat-pusat agama besar dunia; Hindu, Buddha, Islam, Protestan, dan Katolik; keyakinan akan datangnya juru selamat (messiah) yang akan menyelamatkan dunia dari kehancuran adalah inti dari gagasan messianisme. Gagasan ini mewarnai sejarah Indonesia, bahkan hingga masa kontemprer.